Life and strife of modern organic farmers : cases from Sweden, Cambodia, and Bali - Valsecchi, Filippo (SLU/Dept. of Urban and Rural Development, 2019)
Organic farming forms an integral part of the current environmental discourse of “saving the planet” through more ecological forms of cultivation and lifestyle. Yet, beneath this common denominator, the global organic movement encompasses an impressive spectrum of experiences varying along such factors as geographical loca-tion, farm size, work organization, personal attributes, institutional framework, busi-ness style, normative ideals, and farming techniques. Additionally, present-day or-ganic farmers appear to privilege the spheres of individual entrepreneurship and day-to-day farm practice to those of group solidarity and political engagement, which might further question the idea of a unified, full-fledged social movement.